2022
DOI: 10.3389/fpls.2022.847680
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Warming Has Not Affected the Changes in Soil Organic Carbon During the Growing Season in an Alpine Meadow Ecosystem on the Qinghai–Tibet Plateau

Abstract: The effects of climate warming and season on soil organic carbon (SOC) have received widespread attention, but how climate warming affects the seasonal changes of SOC remains unclear. Here, we established a gradient warming experiment to investigate plant attributes and soil physicochemical and microbial properties that were potentially associated with changes in SOC at the beginning (May) and end (August) of the growing season in an alpine meadow ecosystem on the Qinghai–Tibet Plateau. The SOC of August was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
(117 reference statements)
1
4
0
Order By: Relevance
“…This study demonstrated that SOC content varied significantly during seasonal FT, which is similar to the results of previous studies on SOC dynamics under plant growing and non-growing seasons (Boerner et al, 2005;Guo et al, 2018;Wu et al, 2021;Yang et al, 2022b). This may be due to the slow growth rate of vegetation before freezing, which requires fewer nutrients and provides the soil with abundant litter and root residues, facilitating the gradual accumulation of SOC (Wang et al, 2021).…”
Section: Differences In Soil Carbon Pools Between Vegetation Restorat...supporting
confidence: 87%
See 1 more Smart Citation
“…This study demonstrated that SOC content varied significantly during seasonal FT, which is similar to the results of previous studies on SOC dynamics under plant growing and non-growing seasons (Boerner et al, 2005;Guo et al, 2018;Wu et al, 2021;Yang et al, 2022b). This may be due to the slow growth rate of vegetation before freezing, which requires fewer nutrients and provides the soil with abundant litter and root residues, facilitating the gradual accumulation of SOC (Wang et al, 2021).…”
Section: Differences In Soil Carbon Pools Between Vegetation Restorat...supporting
confidence: 87%
“…This difference further results in differences in the amount and type of litter and roots produced by different vegetation restoration types (Feng et al, 2022;Sui et al, 2022), thus altering the SOC content and the transformation trends of the associated pools of organic carbon (Wang et al, 2020a). Studies have shown that forest systems with a complex composition of surface species have a higher capacity for soil water retention and insulation than grasslands (Bo et al, 2021), while their well-developed root systems relax soil compaction, alter soil physical properties (Buyer et al, 2016;Yang et al, 2022b) and provide rich plant and animal residues to the soil. In addition, the density and structure of the underground plant root system also affect the sensitivity of the soil to external hydrothermal conditions (Poulos et al, 2007;Singh et al, 2011), resulting in differences in soil ecosystem carbon cycling processes between vegetation types.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown inconsistent results regarding the responses of soil nutrients to climate warming. While some suggest that warming has no impact on soil C and N contents ( Ning et al., 2019 ; Yang et al., 2022 ), others indicate an increase ( White-Monsant et al., 2017 ). These contradictory results may be attributed to variations in temperature and duration of warming, as well as the diversity of grassland ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in soil nutrients under climate warming can affect plant photosynthesis and physiological characteristics, which may further influence species composition by altering plant facilitation and competitive exclusion (Xu et al, 2022). According to Yang et al (2022), experimental warming did not alter the content of soil organic carbon (SOC) during the growing season in an alpine meadow. Wei et al (2023) demonstrated that plants exhibit consistent adaptive strategies in both above-and belowground traits, favoring more acquisitive traits in warmer environments.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental warming enhanced the pattern of the plant allometric growth and promoted migration of the soil stoichiometric characteristics to deep layers in Beiluhe ( Xu et al., 2022 ). However, in Haibei, Yang et al. (2022) indicated that the warming treatment has not affected the changes in soil organic carbon.…”
mentioning
confidence: 96%